Answer:
y = (x-0)^2 + (-5) ⇒ y = x^2 - 5
Step-by-step explanation:
The general vertex form of the parabola y = a(x - h)² + k
Where (h,k) is the coordinates of the vertex.
As shown at the graph the vertex of the parabola is the point (0, -5)
So,
y = a(x-0) + (-5)
y = ax^2 - 5
To find substitute with another point from the graph like (1,-4)
So, at x = 1 ⇒ y = -4
-4 = a * 1^2 - 5
a = -4 + 5 = 1
<u>So, the equation of the given parabola is ⇒ y = x^2 - 5</u>
Answer:
A=672 m²
Step-by-step explanation:
a²+b²=c² (to find h)
14²+b²=50²
196+b²=2,500
b²=2,304
√b²=√2,304
b=48
h=48
(base×height)÷2
(28×48)÷2
1,344÷2
A=672 m²
Answer:
The answer to your question is:
Step-by-step explanation:
m ∠ 1 = 27°
m ∠ 1 and m ∠ 2 are supplementary
m ∠ 1 + m ∠ 2 = 180°
27° + m ∠2 = 180°
m ∠ 2 = 180° - 27°
m = 2 = 153°